(untitled) (Olhares, 2020)
This article is part of the work-in-progress “Dramaturgies of Playing”, a research in which two classes of children from the “Curumim Program” at SESC Interlagos were observed and recorded by a teacher who is part of the socio-educational team at this branch of SESC São Paulo. The pandemic and its consequences linked to the necro politics established in Brazil nowadays crossed the research and interfered with the view on this material. The relevance of the body’s freedom when playing took a prominent position, along with several similarities between playing and performing, especially in what concerns the construction of bodies and its experiences. The protection of bodies and, consequently, of its knowledges, is a movement of resistance considering the number of lost lives in the current context. The conservation of spaces that allow those bodies to exist collectively is essential for the reinvention of the society about to come.